Oral and sublingual immunotherapy for food allergy. Issue 6 (December 2019) - Nowak-Wegrzyn, Anna; Sato, Sakura; Fiocchi, Alessandro; Ebisawa, Motohiro
Abstract : Purpose of review: To critically appraise the recent most relevant studies in the rapidly advancing field of food oral and sublingual immunotherapy. Recent findings: Food allergen-specific immunotherapy via oral (OIT) and sublingual route (SLIT) increases the threshold of reactivity to peanut, cow's milk, egg, wheat, and many other foods in the majority of the treated individuals. This desensitized state is contingent upon the continued ingestion of the maintenance doses of the food. Permanent oral tolerance is achievable in a smaller subset of the treated individuals. The optimal duration of therapy has not been firmly established but is likely dependent on the phenotype (severity and persistence). Efficacy of food-OIT is superior compared with SLIT, whereas the safety of OIT is less favorable. Standardization of treatment protocols, maintenance dosing, duration of therapy, target populations and harmonization of the outcomes are top priorities at this stage. Summary: OIT and SLIT represent two different routes of food allergen-specific immunotherapy. Although significant progress has been made in the last decade, both treatment modalities are still in the very early stages of development and further investigations are necessary to optimize the protocols and improve safety while maximizing efficacy.